Emerging trends in rhinoplasty education: accelerated adoption of digital tools and virtual learning platforms. Issue 4 (27th August 2022) - McIntosh, Cameron; Patel, Krupa R.; Lekakis, Garyfalia; Wong, Brian J.F.
Abstract : Purpose of review: The COVID-19 pandemic catalyzed the rapid adoption of digital tools and virtual learning platforms by rhinoplasty educators and trainees alike. This review provides an overview of the variety of digital software and web-based tools rhinoplasty educators have adopted and highlights the advantages and potential drawbacks of virtual learning via e-content. Recent findings: Medical education including subspecialty surgical training has recently undergone a dramatic digital transformation. Rhinoplasty surgeon-educators have been forced to embrace new digital tools, including videoconferencing, podcasts, virtual simulation and social media to reach and teach trainees. Recognizing the advantages of this new, limitless digital space, rhinoplasty surgeons are also engaging in virtual transcontinental collaboration and distance mentorship. Summary: The dramatic evolution in how clinical educational materials are now digitally created, curated, disseminated and consumed is likely to far outlast the COVID-19 pandemic itself. Rapid, exponential growth of this digital library, however, places increased responsibility on educators to guide trainees towards evidence-based and state-of-the-art content.